Strategic alliances : coalition building and social movements - Van Dyke, Nella; McCammon, Holly J., 1959- (Social movements, protest, and contention, 2010)
Social researchers in the past have paid surprisingly little theoretical or empirical attention to movement alliances. Strategic Alliances provides a pioneering set of in-depth analyses of the circumstances leading to these organizational alliances. Contributors investigate coalition dynamics among social movements, including antiwar, environmental, and labor movements, as well as ethnic organizations and women's groups. While many of the essays examine coalition formation in the United States, others consider coalitions in Britain, the former East Germany, East Asia, and Latin America.Contrib.